The Bee and the Eagle - Forrest, Alan. author. aut Link
XVII, 295 p.
Keywords: This volume's juxtaposition of the empires of Germany and France in 1806, at the dissolution of The Holy Roman Empire, allows a comparison of their transition towards modernity, explored through the themes of Empire, monarchy, political cultures, feudalism, war and military institutions, nationalism and identity, and everyday experience.